Faktor-Faktor Keberhasilan Manajemen Event dalam Penyelenggaraan Wedding oleh Glow Wedding and Event Planner - Pujani, Ni Made Ditha; Kusumarini, Indah; Widaharthana, I Putu Esa (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2025)
The rising demand for wedding organizer services requires effective and structured event management. However, challenges such as weak internal communication, poor vendor coordination, and inefficient time management are still often encountered. This study aims to identify the key factors influencing successful event management and to analyze the application of POAC (Planning, Organizing, Actuating, Controlling) functions by Glow Wedding and Event Planner in organizing weddings. This research employed a qualitative approach with data collected through in-depth interviews, participant observation, and document analysis. Informants were selected purposively and included the owner and operational staff directly involved in event planning and execution. Thematic analysis based on POAC was used to interpret the data. The results of the study indicate that the success of event management at Glow Wedding and Event Planner is influenced by the effectiveness of internal and external communication, structured time management, optimal vendor coordination, and consistency in service delivery, which serve as key supporting factors in the successful organization of weddings.